2015
DOI: 10.1093/geront/gnv024
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Maintenance of a Community-Based Older Adult Physical Activity Program

Abstract: Assessing the readiness of organizations for program delivery and the match between program goals and the needs of organizations and participants would help facilitate the successful implementation and maintenance of physical activity programs in community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 23 publications
1
38
0
1
Order By: Relevance
“…The literature showed that financial resources/reimbursement, time available, professionals' attitude and support from organization are frequently cited influencing factors to the implementation of a physical activity (promotion) programme in rehabilitation care (18)(19)(20)(21)(22) or in primary healthcare (15,23,24). These factors were also reported by professionals involved in the current study to hamper and/or facilitate the implementation process.…”
Section: Discussionmentioning
confidence: 72%
“…The literature showed that financial resources/reimbursement, time available, professionals' attitude and support from organization are frequently cited influencing factors to the implementation of a physical activity (promotion) programme in rehabilitation care (18)(19)(20)(21)(22) or in primary healthcare (15,23,24). These factors were also reported by professionals involved in the current study to hamper and/or facilitate the implementation process.…”
Section: Discussionmentioning
confidence: 72%
“…Review of the references of one paper led to the discovery of additional papers on older adults' attitudes to falls prevention programmes, which were included [6][7][8] to present views specific to falls prevention activities. So in total, seventeen papers were included: five systematic reviews 5,7,9,10,11 ; three reviews 6,12,13 ; and nine primary studies for context 8,[14][15][16][17][18][19][20][21] .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining primary studies [14][15][16][17][18]20,21 were all qualitative studies that set out to explore attitudes towards different types of strength and balance activities. The study participants were mainly people taking part in specific programmes of resistance exercise; falls prevention programmes; bone strength programmes or general activity programmes with a specific component targeting strength.…”
Section: Sense Of Belonging 4 Increase Social Activity 2 Observing Otmentioning
confidence: 99%
“…(F4: P3) Thus, to effectively increase PA participation within this population, health-promotion strategies should go further than merely educating and raising awareness about potential health benefits, and should also advocate for the provision of low-cost, and easy reachable PA opportunities regardless of financial status (Petrescu-Prahova et al, 2015;Borodulin et al, 2016). It is worth noting that for the participants recruited from the assisted living retirement home, any PA sessions delivered were included within the cost of the overall living fee, and hence lack of financial resources was rejected as a potential barrier for PA participation (Baert et al, 2016).…”
Section: Enabling Correlatesmentioning
confidence: 99%